Determinants of depression among university students in Malaysia; a national cross-sectional study. - Akhtari-Zavare, Mehrnoosh; Mohd Sidik, S; Kotera, Y; Gani, N. A. (Tarbiat Modares University,Danishgah-i Tarbiyat Muddaris, 2023)
Aims: Depression in Malaysia represents a significant and growing public health concern. With the current challenges in academic and university life, university students have become particularly vulnerable to depression and are unable to cope with stress. Accordingly, this study aimed to identify associative factors for depression among Malaysian students. Materials & Methods: A cross-sectional study was conducted at public and private universities in Malaysia. A convenience sample of 1821 out of 1860 cases were approached and completed self-administered questionnaires, regarding depression (Patient Health Questionnaire-9) and their socio-demographic, academic, and psychosocial characteristics. A Chi-square test was conducted to find the relationship between the variables and depression, followed by multivariate logistic regression analysis to identify the predictors. Findings: More than one-third (33.8%) of students scored clinical levels of depression. Financial support for the study, alcohol consumption, poor sleep quality, body mass index, and the global score for psychosocial characteristics were predictors of depression. Conclusion: A high rate of depression in Malaysian students may be mitigated by addressing the influencing factors. Interventions, such as lifestyle change can reduce depression in this group.